(untitled) (The Research of Medical Science Review, 2024)
Introduction:Type 2 diabetes mellitus (T2DM) is the most prevalent type of the diabetes and is typically brought on by an insufficient or resistant response to insulin by the body. Usually, a lack of insulin or a resistance to it results in type 2 diabetes. Around 463 million persons worldwide suffer from diabetes, with type 2 diabetes accounting for 90% of cases. After smoking and high blood pressure, diabetes mellitus is the third most common cause of premature death worldwide, according to the World Health Organization. Methodology: A descriptive cross-sectional study was conducted from April to June 2024 at Liaquat University Hospital, Pakistan. The study assessed knowledge, attitude, and practice (KAP) related to type 2 diabetes mellitus (T2DM) among patients using convenience sampling. Data were collected with a questionnaire adapted from the, American Diabetes Association (ADA's) Diabetes Self-Management Assessment Research Tool (D-SMART). Data analysis was performed using SPSS version 21. Results: A total of 377 type 2 diabetic patients participated in the study conducted at Liaquat University Hospital, Hyderabad. The mean age of respondents was 46, and standard deviation was 12. Among the participants, 53.05% were male and 46.9% were female. According to marital status of participants 90.98% were married, 2.39% were divorced and 6.63% were widow. According to occupation the majority of participants were casual labour 44.8%, 31.65 were formal labour, and 23.6% were unemployed. The overall knowledge of participants regarding diabetic diet, 29% was good while 71% was poor, according to overall Attitude of participants regarding diabetic diet was 45% positive and 55% negative, overall Practice of participants regarding diabetic diet was 19% Good and 81% poor. Conclusion: The study conducted at Liaquat University Hospital Hyderabad revealed significant gaps in knowledge, attitude, and practice(KAP) related to dietary habits among Type 2 diabetic patients. There is a crucial need for focused educational interventions to promote diabetic self- management among these patients, as evidenced by the widespread lack of appropriate dietary practices and positive attitudes about diabetes care despite a moderate degree of awareness.